KONSELING INDIVIDU TEKNIK DISPUTING SEBAGAI UPAYA DALAM MENGATASI SELF BLAMING (MENYALAHKAN DIRI) PADA REMAJA - Rofi'ah, Risatur (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Self blaming is an emotional awareness that every individual has which includes anger, sadness, embarrassing circumstances, despair, when making mistakes that are inflicted by oneself. In general, self-blaming occurs in adolescents. This is because adolescents have unstable emotions. Adolescents who are less able to accept comments from their environment will tend to blame themselves (self-blaming). If self-blaming is not addressed immediately, this will result in low self-esteem and physical disorders. Efforts made to overcome self-blaming are through individual counseling of disputing techniques. one of the theories of Rational-Emotive Therapy (RET) which follows the pattern of the A-B-C theory, emphasizes that problematic behavior is caused by a person's thinking, namely irrational thinking so that the focus of handling this approach is on the individual's thinking and focuses on how the human being thinks, assesses, decides, analyzes, and acts. This study uses a qualitative research method with the type of case study research. The data collection is carried out through interviews, observations, and documentation. Meanwhile, the data analysis technique used is comparative descriptive by comparing theoretical and field data and results before and after counseling is carried out. The results of this study show that there is a change in the counselor's self, namely in the form of self-blaming symptoms which are characterized by a change in a more rational mindset.